Respect Muslim women right to wear hijab at the workplace - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2017)
Like many other religious beliefs, Islam placed high regards to individual's honour and dignity. Guarding chastity and appropriate dressing for the Muslims are guided by their religious beliefs. The criterion of modest dressing for women in the presence of strangers and non-Mahram' is contained in the divine law. It is forbidden that any person should look at the awrah (intimate parts of the body) of another, whether of the same or the opposite sex, and whether with or without desire. For a man, the awrah is from his navel to his knee, while a woman her awrah is her entire body except only her face and hands. Therefore, it is obligatory for a woman to cover her entire body. This article discusses the employer's duty to respect muslim women right to war hijab at the workplace.